2021
DOI: 10.1590/s1517-707620210004.1321
|View full text |Cite
|
Sign up to set email alerts
|

Study of the Life Span of Adhesively Bonded Single Lap Joint Due to Creep

Abstract: Adhesive joints are often used in several areas, including offshore systems and automobiles. The development of suitable models to predict the joint behavior has several challenges, especially due to creep phenomena. The aim of this study is to investigate the creep lifetime of single lap joints considering two different adhesives (epoxy and polyurethane). Long-term tests are performed using a pneumatic creep equipment (PCE). The parameters to the creep model are obtained for each adhesive, where load and life… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 19 publications
0
0
0
Order By: Relevance
“…When the creep load reduces from 80% to 70% of the static strength, the time until rupture increases more than 1700 h (more than 200 times longer). In the same sense, Carneiro Neto et al 103 showed that when the creep load decreased by about 10%, the creep life of SLJs extremely increased. Simões et al 104 performed creep tests in SLJs using an acrylic pressure sensitive adhesive at different creep loads (between 30%-80% of the static strength).…”
Section: Load Levelmentioning
confidence: 86%
See 2 more Smart Citations
“…When the creep load reduces from 80% to 70% of the static strength, the time until rupture increases more than 1700 h (more than 200 times longer). In the same sense, Carneiro Neto et al 103 showed that when the creep load decreased by about 10%, the creep life of SLJs extremely increased. Simões et al 104 performed creep tests in SLJs using an acrylic pressure sensitive adhesive at different creep loads (between 30%-80% of the static strength).…”
Section: Load Levelmentioning
confidence: 86%
“…Carneiro Neto et al 31 also observed substantial differences in the creep life of ENF specimens even with slight variations in the applied creep loads. However, this aspect was not verified in SLJs when a polyurethane adhesive was used, 103 as will be detailed in Adhesive type section.…”
Section: Load Levelmentioning
confidence: 99%
See 1 more Smart Citation